AMBITION OF NATE O'RILEY IN JOHN GRISHAM'S THE TESTAMENT:AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WINDARTI, SRI (2007)
The major problem of this study is to reveal how the major character realizes in ambition. The objectives of this study are to analyze the structural element and to analyze the novel especially the main character based on individual psychological perspective. In analyzing The Testament, the writer uses qualitative method and individual psychological approach. The object of the study is John Grisham's The Testament published in 1998 by Brantam dell. The data sources are primary data and secondary data sources. The primary data source is the novel The Testament itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and psychology, especially an ambition. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, in this novel, John Grisham wants to say that people should realize their ambition, although it is not easy, to make their life better. Second, in the novel, John Grisham wants to illustrate the influences of an ambition on one's life. The last, John Grisham tries to give some valuable lessons to readers such as patience, strength, and hope.